Exome Sequencing Identifies a Rare HSPG2 Variant Associated with Familial Idiopathic Scoliosis. Issue 2 (1st February 2015) - Baschal, Erin E; Wethey, Cambria I; Swindle, Kandice; Baschal, Robin M; Gowan, Katherine; Tang, Nelson L S; Alvarado, David M; Haller, Gabe E; Dobbs, Matthew B; Taylor, Matthew R G; Gurnett, Christina A; Jones, Kenneth L; et al.
Abstract: Idiopathic scoliosis occurs in 3% of individuals and has an unknown etiology. The objective of this study was to identify rare variants that contribute to the etiology of idiopathic scoliosis by using exome sequencing in a multigenerational family with idiopathic scoliosis. Exome sequencing was completed for three members of this multigenerational family with idiopathic scoliosis, resulting in the identification of a variant in the HSPG2 gene as a potential contributor to the phenotype. The HSPG2 gene was sequenced in a separate cohort of 100 unrelated individuals affected with idiopathic scoliosis and also was examined in an independent idiopathic scoliosis population. The exome sequencing and subsequent bioinformatics filtering resulted in 16 potentially damaging and rare coding variants. One of these variants, p.Asn786Ser, is located in the HSPG2 gene. The variant p.Asn786Ser also is overrepresented in a larger cohort of idiopathic scoliosis cases compared with a control population ( P = 0.024). Furthermore, we identified additional rare HSPG2 variants that are predicted to be damaging in two independent cohorts of individuals with idiopathic scoliosis. The HSPG2 gene encodes for a ubiquitous multifunctional protein within the extracellular matrix in which loss of function mutation are known to result in a musculoskeletal phenotype in both mouse and humans. Based on these results, we conclude that rare variants in the HSPG2 gene potentially contribute to the idiopathic scoliosis phenotype in a subset of patients with idiopathic scoliosis. Further studies must be completed to confirm the effect of the HSPG2 gene on the idiopathic scoliosis phenotype.